Writing Descriptive Mapping on students D3 Bahasa Inggris Programs - ELFRIDA BR SILALAHI (JETAL: Journal of English Teaching & Applied Linguistic, 2021)
ABSTRACT This study concerns with the improve students’ creativity ability in writing descriptive paragraph through mind mapping technique. The objective of this study is to discover whether the use of mind mapping could significantly improve students’ creativity ability in writing descriptive paragraph. With support from the theory by Buzan. This study was conducted by applying Classroom Action Research which was carried out in two cycles in 4 meetings. The subject of this study was the Administration Public course in 2ed semester of Students Universitas Merdeka Malang which consisted of 20 students. The data will take in quantitative and qualitative data. Where quantitative data collected by giving descriptive writing tests that related to topic in TA( (tugas akhir) and calculating the mean of students’ scores. The quantities data were collected by the students’ score in (80. 55) which was higher than the first cycle (74.95) and orientation test (69.65). The qualitative data were collected observation and questionnaire sheets. The analyzed qualitative data gathered from the observation and questionnaire sheet during cycle I and II. It was found that students also made improvement students creativity in writing descriptive paragraph by using mapping on their TA (tugas akhir) while guidance and teaching learning proses . Despite all students got problems at 1st meeting, they could handle their difficulties and more enjoy their lesson. By the process they become active and creative in writing descriptive paragraph and qualitative data showed students strongly agreed by mind mapping had solve students problem in writing TA (tugas akhir) that related to writing descriptive paragraph. The result of the research showed that mind mapping significantly improved students’ ability in writing TA (tugas akhir) that related to descriptive paragraph text.